THE EXPRESSION OF POLITENESS AND IMPOLITENESS THROUGH THE FORMS “YOU-SEN” AND “YOU-SIZ” IN ENGLISH AND UZBEK FAMILY DISCOURSE («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, the role and function of "you-sen" and "you-siz" in the expression of politeness and impoliteness in English and Uzbek family discourse is analyzed on the basis of examples.